ELECTROCHEMICAL SENSOR FOR THE DETECTION OF HYDROQUINONE USING A CARBON PASTE ELECTRODE MODIFIED WITH MOLECULARLY IMPRINTED POLY(METHYL RED) (Lantanida Journal, 2026)
Tes
Keywords: carbon paste electrode; hydroquinone; electrochemical sensor; methyl red; voltammetry